THE ADAPTATION STRATEGY OF BIDIKMISI UNIVERSITY STUDENTS OF RIAU IN COMPLETING LECTURE OUTSIDE THE TIME OF RESPONSIBILITY - Abdul Wahid; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Adaptation Strategy of Bidikmisi Students, University of Riau in Completing Study Outside of Dependent Period” has been the title of this study. Researchers are keen to discuss this topic because of the importance of education in developing high-quality human resources, but the issue of cost cannot be overlooked. This study's analysis is descriptive quantitative analysis. Related to the variables and levels of Bidikmisi students' adaption techniques at the University of Riau, which were then studied using the theory of coping strategies. In terms of the problem formulation in this study, namely(1) What are the elements that prevent Bidikmisi pupils from finishing college outside of the dependent period? (2) What is Bidikmisi students' adaption plan for finishing college outside of the dependant period?. A questionnaire will be used to gather data in this investigation. The population and samples in this study were 620 people and 86 samples, as defined by the Slovin formula, and the data analysis indicated that the inhibiting factors in terms of Economics were the most significant., Academics and internal pupils were in the top category, and the tactics utilized were both problem-solving tactics and emotional-focused tactics. Keywords: Adaptation Strategy, Bidikmisi Student, Coping Strategy